(untitled) (Research, Society and Development, 2022)
Adolescent pregnancy is a public health issue, which involves biological, social, economic and cultural aspects. Thus, it is important to understand maternal conditions and risk factors associated with pregnancy at this stage of human development, so that better interventions and clinical practices can be designed. This study aimed to identify maternal conditions and risk factors associated with teenage pregnancy. Therefore, an integrative literature review was carried out, using the PICO strategy. The results showed that this phenomenon has physical, socioeconomic and educational implications for those who experience it. Young mothers usually have losses, which are often preventable, that increase the risk of maternal and child mortality. The conditions of social vulnerability and the lack of family support are highlighted, which increase the risk of adverse situations and negative outcomes. Thus, it is important that health education interventions are carried out so that there is less risk, making women have their children in a more favorable environment.